2003
DOI: 10.1086/378560
|View full text |Cite
|
Sign up to set email alerts
|

New Constraints on ΩM, ΩΛ, andwfrom an Independent Set of 11 High‐Redshift Supernovae Observed with theHubble Space Telescope

Abstract: We report measurements of M , Ã , and w from 11 supernovae (SNe) at z ¼ 0:36 0:86 with high-quality light curves measured using WFPC2 on the Hubble Space Telescope (HST). This is an independent set of high-redshift SNe that confirms previous SN evidence for an accelerating universe. The high-quality light curves available from photometry on WFPC2 make it possible for these 11 SNe alone to provide measurements of the cosmological parameters comparable in statistical weight to the previous results. Combined with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

45
644
4
3

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 1,479 publications
(696 citation statements)
references
References 95 publications
45
644
4
3
Order By: Relevance
“…Precise corrections for dust extinction of eleven more supernovae made possible by accurate HST photometry were shown to support the accelerating expansion and provided tighter constraints on the dark energy equation of state [5]. A sample of high-redshift supernovae reaching z ∼ 1.6 has shown that the supernovae follow the transition from deceleration to acceleration expected as the universe goes from matter domination to dark energy domination [16,5,18]. These space-based measurements have significantly bolstered both the case for dark energy and the efficacy of Type Ia Inner and outer contours delimit 68% and 99% confidence, respectively.…”
Section: Cosmology With Supernova From the Ground And Spacementioning
confidence: 97%
See 2 more Smart Citations
“…Precise corrections for dust extinction of eleven more supernovae made possible by accurate HST photometry were shown to support the accelerating expansion and provided tighter constraints on the dark energy equation of state [5]. A sample of high-redshift supernovae reaching z ∼ 1.6 has shown that the supernovae follow the transition from deceleration to acceleration expected as the universe goes from matter domination to dark energy domination [16,5,18]. These space-based measurements have significantly bolstered both the case for dark energy and the efficacy of Type Ia Inner and outer contours delimit 68% and 99% confidence, respectively.…”
Section: Cosmology With Supernova From the Ground And Spacementioning
confidence: 97%
“…Samples totaling 39 Type Ia supernovae, segregated into early, middle and late host-galaxy morphologies from an HST Snapshot survey, were shown to support an accelerating expansion [20]. Precise corrections for dust extinction of eleven more supernovae made possible by accurate HST photometry were shown to support the accelerating expansion and provided tighter constraints on the dark energy equation of state [5]. A sample of high-redshift supernovae reaching z ∼ 1.6 has shown that the supernovae follow the transition from deceleration to acceleration expected as the universe goes from matter domination to dark energy domination [16,5,18].…”
Section: Cosmology With Supernova From the Ground And Spacementioning
confidence: 99%
See 1 more Smart Citation
“…In the following decade, advances in instrumentation and improved host-galaxy extinction estimators have resulted in precise measurements which rule out dust extinction as an alternative to an accelerating expansion (Riess et al, 2004). Recently direct SN searches, for example with the Hubble space telescope (HST) (Knop et al, 2003), have obtained high quality light curves and are able to constrain the cosmological parameters independently of other datasets. Recent supernovae observations of the distance modulus versus redshift (see Appendix A.1) from the Supernova Legacy Survey (SNLS) and the ESSENCE survey (Miknaitis et al, 2007;Wood-Vasey et al, 2007) are shown in Fig.…”
Section: The Accelerating Expansion Of the Universementioning
confidence: 99%
“…In fact, WMAP measurements together with BAO can completely fix Ω k nearly independently of the dark energy equation of state (Komatsu et al, 2010). As CMB measurements are sensitive to the combination Ω m h 2 , a flatness prior together with constraints on h from HST (Knop et al, 2003) are used to break this degeneracy and obtain good constraints on Ω Λ = 1 − (Ω m h 2 )/h 2 .…”
Section: The Accelerating Expansion Of the Universementioning
confidence: 99%